Control and Teleoperation of Robot Khepera via Android Mobile Device through Bluetooth and WiFi. Issue 25 (2016) - Papcun, Peter; Zolotova, Iveta; Tafsi, Karim
Abstract: The paper describes the design and implementation of applications for control mobile robot Khepera III via mobile device on the platform Android. Communication between the mobile device and the mobile robot was realized through Bluetooth and WiFi interface. The solution of robot control is capable of teleoperation, following line, avoiding obstacles, and face recognition. Application takes a photo with USB camera placed on the robot. Then, this photo is sent to a mobile device, which recognizes a face. This solution demonstrates the use of smart phone as a control unit without use of computer. Image recognition is running on smart phone with Android as the operation system.